Sustainable Built Environment and Urban Growth Management - Wey, Wann-Ming (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nowadays, the sustainable built environment planning in most cities has come to a turning point as the growth in traffic and population has become a serious concern and put tremendous pressure on both the environment and people in these cities. It is therefore important to find new ways or lifestyles-such as compact city, transit-oriented development (TOD) formulations-that are more flexible, inclusive, and sustainable. Furthermore, for the sustainable built environment and urban growth management, not only should the growth management principles-which include smart growth, sustainable growth, and inclusive growth-be taken into account but innovative/smart planning strategies-such as mixed use design, green transport, and new urbanism-are also utilized in planning sustainable built environments in order to prevent the urban sprawl development that has occurred.